Serine 132 Is the C3 Covalent Attachment Point on the CH1 Domain of Human IgG1 - Vidarte, Luis; Pastor, Carlos; Mas, Sebastian; Blázquez, Ana Belen; de los Rio, Vivian; Guerrero, Rosa; Vivanco, Fernando (My University, 2024)
The covalent binding of C3 (complement component C3) to antigen-antibody complexes (Ag Ab; immune com plexes (ICs)) is a key event in the uptake, transport, presentation, and elimination of Ag in the form of Ag Ab C3b (IC C3b). Upon interaction of C3 with IgG IC, C3b C3b IgG covalent complexes are formed that are de tected on SDS-polyacrylamide gel electrophoresis by two bands corresponding to C3b C3b (band A) and C3b IgG (band B) covalent complexes. This allows one to evaluate the covalent binding of C3b to IgG antibodies. It has been described that C3b can attach to both the Fab (on the CH1 domain) and the Fc regions of IgG. Here the covalent interaction of C3b to the CH1 domain, a region previously described spanning residues 125¿147, has been studied. This region of the CH1 domain is ex posed to solvent and contains a cluster of six potential acceptor sites for ester bond formation with C3b (four Ser and two Thr). A set of 10 mutant Abs were generated with the putative acceptor residues substituted by Ala, and we studied their covalent interaction with C3b. Sin gle (Ser-131, Ser-132, Ser-134, Thr-135, Ser-136, and Thr 139), double (positions 131¿132), and multiple (positions 134¿135-136, 131¿132-134¿135-136, and 131¿132-134¿135- 136¿139) mutants were produced. None of the mutants (single, double, or multiple) abolished completely the ability of IgG to bind C3b, indicating the presence of C3b binding regions other than in the CH1 domain. How ever, all mutant Abs, in which serine at position 132 was replaced by Ala, showed a significant decrease in the ability to form C3b IgG covalent complexes, whereas the remaining mutants had normal activity. In addition we examined ICs using the F(ab )2 fragment of the mutant Abs, and only those containing Ala at position 132 (in stead of Ser) failed to bind C3b. Thus Ser-132 is the binding site for C3b on the CH1 domain of the heavy chain, in the Fab region of human IgG.